12 year follow up of enzyme-replacement therapy in two siblings with attenuated mucopolysaccharidosis I: the important role of early treatment. Issue 1 (December 2016) - Gabrielli, Orazio; Clarke, Lorne; Ficcadenti, Anna; Santoro, Lucia; Zampini, Lucia; Volpi, Nicola; Coppa, Giovanni
Abstract Background Mucopolysaccharidosis type I is an autosomal recessive disorder caused by deficiency of α-L-iduronidase and characterized by a progressive course with multisystem involvement. Clinically, Mucopolysaccharidosis type I is classified into two forms: severe (Hurler syndrome), which presents in infancy and is characterized by rapid progressive neurological involvement and attenuated (Hurler/Scheie and Scheie syndromes), which presents with slower progression and absent to mild nervous system involvement. The specific treatment for attenuated Mucopolysaccharidosis type I consists of enzyme-replacement therapy with laronidase (human recombinant α-L-iduronidase, Aldurazyme). We present here the clinical and laboratory results in an 12-year-old patient affected by the attenuated form of Mucopolysaccharidosis type I treated by enzyme-replacement therapy from the age of 5 months, compared with his 17 year old affected sister, who started therapy at 5 years of age. Case Presentation Clinical evaluation of these siblings shows that initiation of therapy prior of the onset of clinically detectable disease resulted in considerable improvement in outcome in the young sibling. After 12 years of enzyme-replacement therapy, facial appearance, linear growth rate, and liver and spleen volumes were normal; moreover, the degree of joint disease, vertebral, and cardiac valvular involvement were only minimal compared with those of his sister. Conclusion This study demonstrates that early diagnosis and early initiation of enzyme-replacement therapy substantially modify the natural history of the attenuated form of Mucopolysaccharidosis type I.